CORRELATION BETWEEN IgE PRODUCTION AND CYTOKINE PATTERN IN PATIENTS WITH IXODES TICK-BORNE BORRELIOSIS - A. I. Simakova; E. V. Markelova (Медицинская иммунология, 2014)
Abstract. With the purpose of establishment of the role of IL-4, IL-13 and IFNγ cytokines in regulation of the general IgE synthesis in serum of patients with different forms of tick-borne borreliosis, 31 patients have been surveyed. The received results have revealed that patients with ITBB irrespective of the level of the general IgE synthesis can be divided into two subgroups. In a subgroup of patients with the increased level of the general IgE, identical dynamics of proinflammatory and anti-inflammatory cytokines, describing the prevalence of the Th2 immune response has been observed. In patients with the reduced level of this antibody the mixed Th1/Th2 type and more smooth course of the illness were observed. Also, direct correlation between high level of the general IgE in serum and IgM titer was shown.